THE ROLE OF PROBLEM EDUCATIONAL TECHNOLOGY IN TRAINING FUTURE TEACHERS - Dildor Eshmurodova (Journal Park Publishing, 2024)
In the article, problem-based learning technology is a teaching system in which the teacher presents a problem situation in the lesson, and the students solve it independently. It is said that technology helps in creative acquisition of knowledge and development of thinking ability. Also, the essence of the effectiveness of this technology in higher education today will be revealed.
Keywords: technology, teaching, problem-based education, technology, communication, effectiveness, student, method.